Stella - Getchell, Robert; Goldwyn, Samuel; Erman, John; Midler, Bette; Goodman, John; Alvarado, Trini; Peldon, Ashley (Touchstone Pictures and the Samuel Goldwyn Co., 1990)
Tough and independent Stella discovers that she is pregnant after a brief affair with a doctor. She raises her daughter Jenny alone in a loving relationship, until Stella realizes that there are advantages that only Jenny's wealthy father could provide.